Patients with anal fistula due to chronic anal fissure: prevelance and treatment - Gulen, Merter; Ege, Bahadır; Sarıyıldız, Gülçin Türkmen (International Surgery Journal, 2021)
Background: The association of an abscess and/or fistula with the fissure is not identification. Data on the treatment strategy is not clear and also indefinite. Methods: The aim of this study was to search for the prevalence of a fistula in patients with chronic anal fissure (CAF). All of the patients were examined by physicians specialized and experienced in proctology. They were registered on standardized forms. Patients who described discharge after chronic anal pain in their anamnesis also worked on these forms. All of the patients included in the study had a CAF and an anal fistula developed on the basis of anal fissure. Results: Patients who underwent surgery for anal fistula between 2011-2020 were analyzed rectospectively. Nineteen patients (2.6%) had a fistula due to CAF. Twelve (62%) of the patients had superficial fistula, 7 (38%) had type 1 fistula. Fistulectomy and internal sphincterotomy were performed in patients with superficial fistula developed on the basis of CAF. In patients with type 1 anal fistula developed on the background of CAF, only fistulotomy was performed. The mean recovery time of the patients was 14 days and the mean duration of symptoms was 4 days. Conclusions: It is the determinant of CAF in the success of the treatment of anal fistula developing on the basis of CAF. Adequate sphincterotomy is successful in the treatment of CAF and anal fistula developing on the fissure background.